Manajemen Monitoring Pembelajaran Berbasis E-Learning (Studi Kasus Di SMK Raden Patah Mojosari) - Jupri Abusin; Syahrul Ode aliani; Muhammad Husnur Rofiq (Pedir Research Institute, 2021)
Abstract: Monitoring is the process of collecting data/information and analyzing it based on predetermined indicators regarding school programs or activities to be corrected for the improvement of school programs or activities. The purpose of this study is to 1) analyze the implementation of monitoring management on e-learning-based learning. 2) analyze the implications of monitoring management on e-learning-based learning. This study uses a qualitative research approach, with a managerial type or more generally with the term management approach. The subjects in this study were the Principal, Deputy Principal, Engineering Teachers, Students. The results of the study show that, 1) Implementation of Monitoring on E-Learning-Based Learning: (a) Planning for Learning Monitoring. First, preparation of Human Resources (HR). Second, e-learning training for all those involved in learning that is applied at SMK Raden Patah Mojosari. (b) Implementation of Learning Monitoring. First, the implementation phase of monitoring e-learning learning (Creation of lesson plans, selection of WEB-based Computer, HP and Laptop Media). Second, approach (using applications, WA, Classroom, Moodle, Zoom). Third, learning monitoring methods (direct or real-time learning and web-based or web-based indirect learning). Fourth Internet network, Fifth, Student Motivation, Sixth Facilities and infrastructure. (c) Evaluation of learning monitoring. 2) Monitoring Implications for E-Learning-Based Learning is divided into two, namely; (a) the impact of monitoring e-learning on teachers, (b) the impact of monitoring e-learning on students. The monitoring implications of e-learning-based learning are divided into two, namely; a) the impact of monitoring e-learning learning on teachers, b) the impact of monitoring e-learning on teachers.